TRADISI SIAT API DI DESA PAKRAMAN DUDA KECAMATAN SELAT KABUPATEN KARANGASEM (PERSPEKTIF PENDIDIKAN AGAMA HINDU) - Eko Adi Saputra; I Nyoman Temon Astawa; Ida Bagus Komang Sindu Putra (UHN IGB Sugriwa Denpasar, 2020)
Pakraman Duda village has a very interesting tradition, which is a kind of fire game using tools in the form of dry coconut leaves/danyuh that are burned. This tradition is carried out once a year on Tilem Sasih Kawolu Nemu Kajeng Kliwon with the aim of melting and destroying the nature of blind kala that exists in humans. The results of this study will show that the implementation of the fire fighting tradition begins with preparation, metektek prus, at the temple and at their respective homes, then the participants go to the fire fighting tradition arena complete with weapons in the form of prakpak / danyuh, the function of which aims to appeal to Sanghyang Widhi's idea. Wasa (almighty god) so that he gives inner and outer strength, neutralizes negative forces, and to melt and destroy Butha Kala's qualities which in humans, fire in prakpah or danyuh is a symbol of destroying bad qualities such as anger, jealousy human heart, envy, and greed. Hindu religious education contained in the Siat Api tradition in Pakraman Duda Village, namely the value of tattwa education, the value of social education, and the value of ceremonial education.